The risks of self-medication in elderly patients with Elderly patients with hypertension: A review of health impacts (Research, Society and Development, 2024)
The main aim of this study was to analyze the risks of indiscriminate use of antihypertensive drugs in elderly people with a history of the disease A systematic, exploratory and qualitative literature review was therefore carried out Data was collected from PubMed and Scielo using the following descriptors: self-medication, elderly, hypertension and risks The search was conducted in Portuguese and English, using AND as a connector, and included scientific articles published between 2019 and 2024 Ten studies passed the inclusion filter and were directly related to the topic The results of the study showed that hypertension is a significant risk factor for several serious conditions, such as heart disease and stroke The condition is particularly prevalent in the elderly population and is associated with an increase in arterial stiffness and cardiovascular complications Thus, it can be concluded from the existing data that, although many elderly people have access to health services, they still face difficulties that lead them to opt for self-medication.